2017
DOI: 10.5210/ojphi.v9i2.7985
|View full text |Cite
|
Sign up to set email alerts
|

Applications of information and communications technologies to public health: A scoping review using the MeSH term “public health informatics”

Abstract: Objective: To investigate the public health domains, key informatics concepts, and information and communications technologies (ICTs) applied in articles that are tagged with the MeSH term "public health informatics" and primarily focus on applying ICTs to public health.Materials and Methods: The MeSH term "public health informatics" was searched on MEDLINE-PubMed. The results of the search were then screened in two steps in order to only include articles about applying ICTs to public health problems. First, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…As expected in this section of the Yearbook, the use of digital sources for infectious diseases surveillance leads to many research reports 11 . The originality here is the use of data coming from the EHR 12 , Twitter 8 , or the climate data produced by the US National Aeronautics and Space Administration (NASA) with software 13 dedicated to following the occurrence of infectious disease epidemics of either influenza 8 12 or malaria 13 .…”
Section: Outlook and Conclusionmentioning
confidence: 77%
“…As expected in this section of the Yearbook, the use of digital sources for infectious diseases surveillance leads to many research reports 11 . The originality here is the use of data coming from the EHR 12 , Twitter 8 , or the climate data produced by the US National Aeronautics and Space Administration (NASA) with software 13 dedicated to following the occurrence of infectious disease epidemics of either influenza 8 12 or malaria 13 .…”
Section: Outlook and Conclusionmentioning
confidence: 77%
“…Population health can have the most impact on health informatics research. Recently, Bhattarai et al [ 10 ] investigated how information and communications technologies (ICTs) were applied to public health and found that “communicable disease monitoring,” “public health policy and research,” and “public health awareness” are the most common public health domains interacting with ICTs. One of the limitations of their study is that, by only using one MeSH tag as a selection criterion, publications without the “public medical informatics” MeSH term were excluded from their dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness and safety of HIT must be evaluated scientifically before it can be used by doctors, patients, and consumers. For example, Bhattarai et al [ 10 ] reported that inconsistent results exist regarding the validity of most of the informatics indicators when various predictors are used for disease surveillance and emergency monitoring, such as syndromic surveillance, dispatch calls, over-the-counter drug sales, and school absenteeism. They suggest additional studies should be conducted to further investigate the validity of such predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the view of bibliometric analysis, [23] documents can be organized by theme (e.g., BC) on a topical entity (e.g., author or affiliated country) for a specific feature (e.g., citations and publications). The subthemes can be determined by clustering medical subject headings (MeSH terms) [24,25] using social network analysis (SNA). [26,27] The second motivation was to investigate what subthemes (denoted by MeSH terms) were different in proportional counts between China and the United States.…”
Section: Different Article Themes Conducted In Countriesmentioning
confidence: 99%